Kualitas Minuman Herbal Kulit Pisang Raja Bulu (Musa paradisiaca L.) pada Suhu Pengeringan Berbeda - Herly Dwi Lestari; Sukarsono Sukarsono; Riomil Latifa; Husamah Husamah (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
Banana peels have not been utilized optimally, just disposed of as organic waste or used as animal feed. Ripe banana peel skin is rich of chemical compounds which are antioxidants, both flavonoid compounds and other phenolic compounds. Banana peel contains high antioxidant activity compared to meat, especially “Raja Bulu” banana skin which has antioxidant equal to 97,85%. Natural source of antioxidants in banana peel skin is very beneficial for health. The purpose of this study was to determine the effect of various drying temperature on antioxidant activity and the optimum drying temperature to antioxidant activity. This study also aims to determine the level of panelist's preference for herbal drinks of “Raja Bulu” banana peel with various drying temperatures. The type of research used is True Experimental Research. The study design was using RAL with 4 treatment P0 (control), P1 (drying temperature 75°C), P2 (drying temperature 80°C), P3 (drying temperature 85°C). Data is included the amount of antioxidant activity content and the average of organoleptic properties of banana peel herbal drink. Data analysis techniques used are One Way Anova and qualitative descriptive. The results showed 1) Various drying temperature effect on the antioxidant activity of banana peel herbal drink. 2) The best treatment is P3 (drying temperature 85°C) with antioxidant activity of 84.87%. 3) The result of the panelist's favorite test for the best color, flavor and taste on P3 treatment with 85 ° C drying temperature.